Engineered hydrophobic pocket of (S)-selective arylmalonate decarboxylase variant by simultaneous saturation mutagenesis to improve catalytic performance. Issue 12 (2nd December 2015) - Yoshida, Shosuke; Enoki, Junichi; Kourist, Robert; Miyamoto, Kenji
Abstract: A bacterial arylmalonate decarboxylase (AMDase) catalyzes asymmetric decarboxylation of unnatural arylmalonates to produce optically pure ( R )-arylcarboxylates without the addition of cofactors. Previously, we designed an AMDase variant G74C/C188S that displays totally inverted enantioselectivity. However, the variant showed a 20, 000-fold reduction in activity compared with the wild-type AMDase. Further studies have demonstrated that iterative saturation mutagenesis targeting the active site residues in a hydrophobic pocket of G74C/C188S leads to considerable improvement in activity where all positive variants harbor only hydrophobic substitutions. In this study, simultaneous saturation mutagenesis with a restricted set of amino acids at each position was applied to further heighten the activity of the ( S )-selective AMDase variant toward α-methyl-α-phenylmalonate. The best variant (V43I/G74C/A125P/V156L/M159L/C188G) showed 9, 500-fold greater catalytic efficiency k cat / K m than that of G74C/C188S. Notably, a high level of decarboxylation of α-(4-isobutylphenyl)-α-methylmalonate by the sextuple variant produced optically pure ( S )-ibuprofen, an analgesic compound which showed 2.5-fold greater activity than the ( R )-selective wild-type AMDase. Graphical abstract: : Using structure-guided directed evolution, the catalytic efficiency of ( S )-selective arylmalonate decarboxylase variant could be increased up to 9, 500-fold.